2017
DOI: 10.1371/journal.pone.0180430
|View full text |Cite
|
Sign up to set email alerts
|

PA21, a novel phosphate binder, improves renal osteodystrophy in rats with chronic renal failure

Abstract: The effects of PA21, a novel iron-based and non-calcium-based phosphate binder, on hyperphosphatemia and its accompanying bone abnormality in chronic kidney disease-mineral and bone disorder (CKD-MBD) were evaluated. Rats with adenine-induced chronic renal failure (CRF) were prepared by feeding them an adenine-containing diet for four weeks. They were also freely fed a diet that contained PA21 (0.5, 1.5, and 5%), sevelamer hydrochloride (0.6 and 2%) or lanthanum carbonate hydrate (0.6 and 2%) for four weeks. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…These findings were also reported by Yaguchi et al . [ 39 ], who demonstrated that PA21 treatment suppressed osteoid formation, fibrosis and porosity in rats with CKD. In the PA21-treated rats, the mineralization lag time and adjusted apposition rate did not substantially differ from those of the vehicle-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also reported by Yaguchi et al . [ 39 ], who demonstrated that PA21 treatment suppressed osteoid formation, fibrosis and porosity in rats with CKD. In the PA21-treated rats, the mineralization lag time and adjusted apposition rate did not substantially differ from those of the vehicle-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation could be the peculiar feature of the experimental model. Adenine can induce elevation of serum calcium, as described in other studies, because in addition to inducing CKD, it acts directly on osteoblasts compromising their mineralization capacity, inducing a severe bone disease with high remodeling rate [35][36][37] .…”
Section: Discussionmentioning
confidence: 72%
“…The absence of correlation between the trabecular volume and BD can be explained by the unique features of the adenine model. Adenine acts directly on osteoblasts compromising the cells capacity of mineralization and inducing a relative hypercalcemia and a high-turnover bone disease [35][36][37] . In our study, we found an increased osteoid surface evidencing compromised bone calcification; however, we also identified high bone reabsorption characterized by the increased osteoclast surface.…”
Section: Discussionmentioning
confidence: 99%
“…Since hyperphosphatemia restricts the use of VDRAs and is associated with mortality of patients with SHPT , the appropriate control of serum P is a foundation of treatment of SHPT. Studies of the effects of phosphate binders on the parathyroid gland in uremic rats have shown improvement of parathyroid gland enlargement with PTH suppression, and reduced parathyroid cell proliferation and bone abnormality by sevelamer hydrochloride ; suppression of PTH expression, inhibition of PTH gene stabilization, and an increase in sensitivity of CaSR to Ca by lanthanum carbonate ; PTH suppression and parathyroid cell proliferation by ferric citrate ; and suppression of PTH, FGF23, and bone disease by sucroferric oxyhydroxide . However, clinically, treatment of hyperphosphatemia using a Ca‐containing phosphate binder raises the risks of hypercalcemia and vascular calcification .…”
Section: Treatment Of Shptmentioning
confidence: 99%